Moisture Characteristics of Biocomposites from PVA/Cassava Starch Reinforced by Lemon Peel Fiber - Pradiza, Revvan Rifada; Junus, Salahuddin; Asrofi, Mochamad; Ilyas, Rushdan Ahmad (Journal of Fibers and Polymer Composites, 2025)
This study reports the moisture absorption and surface morphological characteristics of Polyvinyl Alcohol (PVA) and cassava starch biocomposite with lemon peel fiber as reinforcement. Biocomposite is produced by film casting method. The addition of lemon peel fiber decreases moisture absorption properties. The lowest moisture absorption is 53,37 % for PVA/Cassava starch with 4% lemon peel fiber. This result is much lower than PVA and PVA/starch. Good adhesion of interfacial bonding and the compact structure of the biocomposite thus reduce the moisture absorption. From these results, the created biocomposite can serve as an environmentally friendly alternative.